Linearity of Diameter and Height to Biomass and Carbon Storage of Gmelina arborea in Mirring Village Community Forest - Irundu, Daud; farid karim, Faradilah (Universitas Andi Djemma Palopo, 2025)
Biomass and carbon are forest products stored in plants as a result of photosynthesis. Gmelina arborea, as a community forest plant in Mirring Village, produces biomass and stored carbon, influenced by various factors including diameter and plant height. The purpose of this study was to analyze the linear relationship between the diameter and height of Gmelina arborea and its biomass and stored carbon. The method used was a survey and measurement of the diameter and height of 35 Gmelina arborea trees, followed by an analysis of their linearity and the coefficient of determination (R²) generated from the relationship analysis. The results showed a very strong linear relationship between diameter and biomass and stored carbon, and a fairly strong relationship between height and biomass and stored carbon. The R² values from both relationship analyses were 0.741 and 0.908, respectively. This indicates that the diameter and height of Gmelina arborea can explain the variation in biomass and stored carbon values well.